A randomized control trial comparing peginterferon-α-2a versus observation after stopping tyrosine kinase inhibitor in chronic myeloid leukemia with deep molecular response for at least two years - Kuan, Jew-Win; Chang, Kian-Meng; Loh, Weng Khean; Phan, Chin Lee; Wong, Shu Ping; Chai, Alvin Jung Mau; Yong, Kar Ying; Voon, Kit Kian; Lim, Soo Min; Toh, See Guan (2016)
Background: There is much advancement in treatment of chronic myeloid leukemia (CML) since the approval of first tyrosine kinase inhibitor (TKI), imatinib, by US FDA in 2001. One of them is definitely the concept of stopping TKI, starting at the CML patients who have achieved deep molecular response (MR) of MR4.5 for a reasonable long period of at least two years, pioneered by the researchers from French and Australia. Meanwhile, interferon, the standard treatment of CML before the era of TKI, showed that interferon-responded patients may indeed retain the response once interferon was withdrawn via interferon-induced immunity towards the leukemic clone. This is further supported by stop trial in Japan, in which after stopping TKI, interferon was given for 2 years and it showed a higher drug-free rate compared to stop trial from French and Australia. Hence, it is logical to postulate the use of interferon after TKI was stopped when patients have attained deep MR for more than two years will increase the percentage of patients remain TKI-free on follow-up.